Antígeno leucocitário bovino (BoLA) de classe I e perfil de TNF-α e TGF-β1 na placenta bovina durante a gestação - Gallo, Juliana Martins da Silva (2012)
The purpose of this study is to evaluate the amount of transcripts from the Major Histocompatibility Complex (MHC) class I classical (BoLA-N *) and non-classical (BoLA-NC*), as well as of TNF-α (Tumor Necrosis Factor alpha) and TGF-β1 (Transforming Growth Factor beta 1) cytokines in bovine non-pregnant uterus, caruncles, cotyledons and blastocysts throughout the pregnancy period, in order to understand the immune and physiological mechanisms that occur in pregnancy in cows. The samples were analyzed by qPCR, the qualification (presence or absence) by conventional RT-PCR and the immune fluorescence with sheep monoclonal antibody against MHC class I. As positive control we used a sample of tissue from the bovine lymph node and/or spleen in all experimental tests. The amount of transcript BoLA-N* and BoLA-NC* was small (fold change 0 to 3) in blastocysts and cotyledons. Cotyledons transcription BoLA-NC* is greater than the transcription of BoLA-N*. Blastocysts transcription of BoLA-N* was higher than BoLA-NC*. Blastocysts transcribed more BoLA-NC2 than in cotyledons. Blastocysts not transcribed BoLA-NC4. Cotyledons transcribed BoLA-NC4 more than BoLA-NC2. The caruncles showed large amounts of transcripts (fold change 5 to 400), which were higher for pregnancy period of \"8-9\" month to BoLA-N* and one month for BoLA-NC*. Caruncles BoLA-NC2 transcription was higher than the BoLA-NC4. The uterus non pregnant had fewer transcripts BoLA-N* and BoLA-NC* than in caruncles. The uterus non pregnant no have transcripts of BoLA-NC2, but they had a small amount of transcripts of BoLA-NC4. Caruncles had large amounts of transcripts (fold change 50 to 500) of BoLA-NC2 with pregnancy age greater than one month; those are seemed to protect the fetus from rejection. TNF-α appears in greater amount in late gestation (8 and 9 months), showing the beginning of an inflammatory reaction, necessary to the adequate removal of the fetus and the placenta during delivery. Since TGF-β1 has a peak of expression in the sixth and seventh months of gestation, just when the fetus has its greatest growth, demonstrating a probable involvement of this cytokine in this phenomenon.